1985
DOI: 10.1128/mcb.5.3.569
|View full text |Cite
|
Sign up to set email alerts
|

Abundant nuclear ribonucleoprotein form of CAD RNA.

Abstract: Previous studies of large nuclear ribonucleoproteins (RNPs) containing mRNA and precursors of mRNA have been hampered by the heterogeneity of the material. Any one molecular species of RNA is generally present at a level of less than 1% of the total. Biochemical information about large nuclear RNPs is therefore limited to bulk properties, for the most part derived from analysis of a breakdown product of the RNP that sediments at about 30S in a sucrose gradient. This 30S complex, made up of a fragment of RNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 30 publications
3
61
0
Order By: Relevance
“…The full-length 150-kDa form of ADAR1 was found in a broad peak around the 200S region of the gradient (Fig. 1A Upper), where specific nuclear pre-mRNAs have been shown to sediment (19,(38)(39)(40). The more abundant shorter (110 kDa) form of ADAR1 had a broader distribution, with significant level sedimenting at the 200S and 70S regions of the gradient ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The full-length 150-kDa form of ADAR1 was found in a broad peak around the 200S region of the gradient (Fig. 1A Upper), where specific nuclear pre-mRNAs have been shown to sediment (19,(38)(39)(40). The more abundant shorter (110 kDa) form of ADAR1 had a broader distribution, with significant level sedimenting at the 200S and 70S regions of the gradient ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In previous experiments, fractions corresponding to the analogous positions in the gradient were enriched for the five spliceosomal U snRNAs (37,(39)(40)(41) (Fig. S1D), various pre-mRNAs (36,42,43), and regulatory splicing factors (41,44,45) (Fig. 1E) and contained active spliceosomes (37).…”
Section: Resultsmentioning
confidence: 99%
“…This should not be surprising, because the splicing machinery of a living cell is expected to package and process multi-intronic pre-mRNAs, rather than the mono-intronic pre-mRNAs, which are typically used to assemble spliceosomes in vitro. Indeed, we have shown that several specific nuclear pre-mRNAs and their splicing products, as well as the general population of nuclear poly(A) + RNA, are packaged in compact large nuclear RNP (lnRNP) particles that invariably sediment at the 200S region in sucrose gradients (31)(32)(33)(34) …”
mentioning
confidence: 99%